Method of the numerical solution of a task of distribution of current for wire antennas by method of the integrated equations - Yu. N. Egorov; V. V. Gladeychuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The method of the numerical solution of a task of distribution of current for wire antennas of any geometry is offered. The method differs in a universality combination in relation to geometry of a radiator, high reliability of the decision and a possibility of full automation of calculations. The assessment of reliability is executed by the solution of a test task for the linear symmetric vibrator.